Analisis Foto Jurnalistik Jerit Petani Lada Dalam Pusaran Tambang Timah Karya Nopri Ismi - Ikhsan , Muhammad Aidil; Duku, Sumaina; Muslimin, Muslimin (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This thesis is entitled "Photojournalistic Analysis of the Screams of Pepper Farmers in the Whirlpool of Tin Mine by Nopri Ismi". The formulation of the problem discussed in this thesis is about the meaning of denotation, connotation, and myth as seen from Roland Barthes' semiotic method in photographs by Nopri Ismi. The purpose and purpose of this research was to find out the meaning of denotations, connotations, and myths in the photo of Pepper Farmer Screams in the Tin Mine Whirlpool by Nopri Ismi. The research method used in this study is qualitative research method. The data collection technique uses direct observational observations carried out on the Mongabay.co.id website by observing and collecting photos of Pepper Farmer Screams in the Tin Mine Whirlpool by Nopri Ismi. The interview was conducted by asking questions directly to related parties, namely Nopri Ismi as the photographer, as well as documentation to see important documents and data related to the researcher's problem. The number of photos analyzed in this study amounted to four photos, the photos were analyzed using Roland Barthes' semiotic theory which found results in the form of denotational meanings that describe the circumstances, behaviors, actions, and attitudes that occur in photos. Then there is no connotation stage regarding the Trick Effect (Photo Manipulation). So that it can be ascertained the authenticity and truth that happened to 4 photos by Nopri Ismi according to photojournalism rules. And for the meaning of myth describes reality, sadness, resignation, and situations of truth that occur.